Khind Holdings Berhad / Muhamad Faris Farhan Fauzi - Fauzi, Muhamad Faris Farhan (2022)
This subject is an attempt for student to know how to understand and study the business theory of a certain company that can be put into practical situation. Hence as for me I was giving an opportunity to study on the business theory and rules which run an electrical and electronic appliances manufacturer product which is Khind Holdings Berhad company based in Malaysia. In the first section, I need to study on the purpose of this case study and the problem statement faced by this company. Next section, I was giving a task to study on their company background and choose a product from their company and figure out on how the product works in term of technology parts. Plus, I also collect the information on how KHIND dealing and manage their business strategy in achieving their business goals and perform an effective management. Most information I collected from their company’s website and few secondary sources as well to supports all the facts. In this case study, I analyzed the strength, weakness, opportunities and threats of this company in real business using SWOT analysis. Thus, in the last section I was given to came out with few solutions that can overcome or improve the need and demand from consumers.